IN VIVO EFFECT OF RUTA CHALEPENSIS EXTRACT ON HEPATIC CYTOCHROME 3A1 IN RATS - Martínez-Pérez, Edith Fabiola; Hernández-Terán, Fernando; Serrano-Gallardo, Luis Benjamín (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Since the time when drugs began to be used, it became evident that they could produce a therapeutic effect, but also a clinical condition of toxicity or no effect at all on humans, despite using the same doses in different patients. Such untoward effects were termed “drug idiosyncrasy” and also “idiosyncratic drug effects”, but the factors producing such diverse responses were never taken into account. Materials and Methods: Ruta chalepensis L. (fringed rue) is an herbaceous plant of the Rutaceae family used in traditional medicine due to its properties, such as its analgesic and antipyretic effects. This study used 25 male rats divided into five groups. Plant extract was administered to Groups 1 and 2 at doses of 100 and 30 mg/kg/day, respectively, for three days; Group 3 was administered 100 mg/kg/day of dexamethasone (DEX), as well as 100 mg/kg/day of Ruta chalepensis extract; Group 4 was administered 100 mg/kg/day of DEX and treated as positive control; Group 5 was treated as negative control and was administered a physiological solution. Twenty-four hours after the the last dose, the animals were sacrificed and their livers were extracted. Results: The aqueous extract of Ruta chalepensis, intraperitoneally administered, was able to induce cytochrome 3A1 in doses of 30 mg/kg/day, and a greater inducing effect occurs when the plant is co-administered in doses of 100 mg/kg/day with dexamethasone. Conclusion: This study suggests that aqueous extract of Ruta chalepensis can induce cytochrome 3a1. This study helps provide a better understanding of CYP3a regulation. Future in vitro work is needed to determine the compounds that produce the cytochrome modulation.